Coping Styles, Mental Health, and the COVID-19 Quarantine: A Nationwide Survey in Poland - Kołodziejczyk, Agata; Misiak, Błazej; Szcześniak, Dorota; Maciaszek, Julian; Ciułkowicz, Marta; Łuc, Dorota; Wieczorek, Tomasz; Fila-Witecka, Karolina; Chladzinska-Kiejna, Sylwia; Rymaszewska, Joanna (Frontiers in Psychiatry, 2021)
Background: The outbreak of the novel coronavirus COVID-19 that began from March 2020 is yet to be contained. Consequences of the ongoing pandemic may have a negative impact on the mental health of affected individuals. This particularly refers to those quarantined. Since the COVID-19 pandemic is currently one of the biggest health issues worldwide, a higher demand emerges for research concentrating on the worsening of psychological well-being among the general and the quarantined population, as well as on individual coping strategies that may moderate the occurrence of psychopathologies. Method: Data were collected within the first weeks of the COVID-19 pandemic in Poland. Participants represented quarantine(+) and quarantine(-) groups. To measure psychopathological symptoms a General Health Questionnaire (GHQ-28) was used. For measuring PTSD symptoms Impact of Event Scale- Revised (IES-R) was used. This study followed the coping strategies manifested among the participants using the MiniCope questionnaire. Results: A total of 2036 individuals participated in this study. Quarantine(+) individuals had significantly higher total and subscales GHQ-28 scores (anxiety, insomnia, and somatic symptoms) as well as a higher IES-R arousal score. The quarantine(+) individuals were more likely to use self-distraction as a coping strategy. This research identified positive and negative correlations between presented coping styles and manifested psychopathology. Conclusion: This nation-wide study suggests the deterioration of mental health due to the COVID-19 pandemic and quarantine. This deterioration is observed on most of the measured psychopathological symptoms. The present research provides a line of action that should be followed in the future in case of another epidemic and in the event restrictions like quarantine have to be introduced again.